Gregor Krek in začetki slavistike na Univerzi v Gradcu - Kernbauer, Alois (Traditiones (Ljubljana), 2006)
Gregor Krek's activity and scholarship belong to the era when Slavic philologywas institutionalized as a field as part of general efforts in Indo-European linguistics at universities in Central Europe, including at the "university serving the south and southeast part of the empire" - that is, the University of Graz.
Keywords: Krek, Gregor, 1840-1905; biografije; visoko šolstvo; univerze; Slavic studies; slavistika